Cation Xanthated Exchangers from Colombian Sub Bituminous Coals Effectively Removed Cadmium and Lead fromAqueous Solutions. - Gómez de Arco, Lewis; Alzate Rodríguez, Liliana; Colpas Castillo, Fredy; Fernández Maestre, Roberto (2011)
In Colombia, low rank coals are almost totally used for power and metallurgical aims, which are activities that produce contamination. In this Investigation, as an altemative to the traditional use of low rank coals, we prepared cationic xanthated exchangers from. a subbituminous coal (67.6% e, 4.6% H, 22.4% O. 0.6% S, 3.2% ashes and 46.2% volatile matter) of Montelibano-Córdoba; this exchanger showed betterexchange capacities for cadmium and lead (1.8 meq/g) Iban traditional sulphonated exchangers (0.56 and 1.11 meq!g for cadmium and 1ead respectively). Xanthation was verified at 30 oc and at 5-10 oc witb NaOH and CS2. The best performance ofxanthation, determined by Infrared spectrometry and ion exchange experiments, occurred at low temperatures maybe due to CS2 volatility. By djm;njshjng tbe particle size of coa! th.e exchange capacity increased. Tbe exchange capacitywas evaIuated by flame atomic absorption spectrometry.